The Role of Mineral Fillers in The Process of Structure Formation in Model Systems СASO4 2H2O- Microfiller -H2O - Turemuratov Sharibay Naurizbayevich; Abilova Amina Zhanabaevna; Karlibaev Islambek Bazarbaevich; Niyazimbetova Sultanate Alliyarovna (Genius Journals, 2023)
The influence of fillers on the processes of structure formation in the CaSO4 2H2O - Microfiller – H2O system was studied. It is shown that with an increase in the concentration of the microfiller, the strength of coagulation contacts filler-filler becomes predominant and, in accordance with the nature of the introduced filler, the integral strength either increases (finely ground quartz sand) or drops sharply (kaolin).
Keywords: gypsum; binders; calcium sulfate